Study of the Distributional Performance of Piped Water Consumption Subsidies in 10 Developing Countries - Abramovsky, Laura (World Bank, Washington, DC, 2020)
This paper provides new evidence on how effectively piped water consumption subsidies are targeting poor households in 10 low- and middle-income countries around the world. The results suggest that, in these countries, existing tariff structures fall short of recovering the costs of service provision, and the resulting subsidies largely fail to achieve their goal of improving the accessibility and affordability of piped water for poor households. Instead, the majority of subsidies in all 10 countries are captured by the richest households. This is in part because the most vulnerable population segments typically face challenges in accessing and connecting to piped water services. The paper also reveals shortcomings in the design of the subsidies, which are conditional on poor households being connected to a piped network.